2015
DOI: 10.1038/bmt.2015.74
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of CDX-301, recombinant human Flt3L, at expanding dendritic cells and hematopoietic stem cells in healthy human volunteers

Abstract: Fms-like tyrosine kinase-3 ligand (Flt3L) uniquely binds the Flt3 (CD135) receptor expressed on hematopoietic stem cells (HSC), early progenitor cells, immature thymocytes, and steady state dendritic cells (DC) and induces their proliferation, differentiation, development and mobilization in the bone marrow, peripheral blood, and lymphoid organs. CDX-301 has an identical amino acid sequence and comparable biologic activity as the previously-tested rhuFlt3L which had discontinued clinical development over a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 20 publications
4
86
0
1
Order By: Relevance
“…29 Of note, a recombinant human Flt3L has recently shown to be safe and effective for PBSC mobilization in healthy donors. 39 In conclusion, our study shows that the dose of iNKTs in a G-CSF-mobilized PBSC graft is associated with improved GPFS, highlighting the beneficial role of iNKTs on the usually antagonistic GVHD and GVT effects. However, confirmatory studies on larger numbers of patients are required to confirm this beneficial role and to decipher the respective GVT effect of iNKTs on both myeloid and lymphoid malignancies.…”
Section: Discussionmentioning
confidence: 87%
“…29 Of note, a recombinant human Flt3L has recently shown to be safe and effective for PBSC mobilization in healthy donors. 39 In conclusion, our study shows that the dose of iNKTs in a G-CSF-mobilized PBSC graft is associated with improved GPFS, highlighting the beneficial role of iNKTs on the usually antagonistic GVHD and GVT effects. However, confirmatory studies on larger numbers of patients are required to confirm this beneficial role and to decipher the respective GVT effect of iNKTs on both myeloid and lymphoid malignancies.…”
Section: Discussionmentioning
confidence: 87%
“…5A). Indeed, these three genes code for molecules implicated in the extravasation of thymus-seeding progenitors across corticomedullary junction venules and the expansion of early thymocyte progenitors (ETP) (43)(44)(45). From the analysis of cluster #1, we therefore conclude that thymic MCs show higher expression of genes instrumental in clearance of apoptotic thymocytes by macrophages, maintenance of a noninflammatory milieu, and attraction-expansion of ETPs.…”
Section: Ipa Analyses Of Degs Preferentially Expressed In a Single MCmentioning
confidence: 87%
“…6,49 Experience using FL in the allogeneic HCT setting is largely limited to pre-clinical studies in which FL has been shown to modulate GvHD 50,51 and to augment thympoiesis and T-cell reconstitution 52 to confer protective antiviral immunity 53 in mice and to enhance donor HSC engraftment in dogs. 54 Of interest, comparing PB murine LSK (Lin − Sca-1 + c-kit + ) HSC mobilization following administration of G alone, FL alone, P alone, FL+P and G+P, He et al 55 recently showed that FL+P mobilized the most LSK cells, which produced more colony-forming units and expanded the greatest numbers of PB NK, Treg and conventional and plasmacytoid DCs.…”
Section: Hsc and Pdc Mobilization And Engraftmentmentioning
confidence: 99%
“…Recombinant human FL alone 49 or in combination with perixafor 55 is emerging as an alternative HSC mobilization regimen to G following chemotherapy. Given its NK and DC induction, recombinant human FL may offer a novel means to enhance both HSC and pDC expansion and to augment innate immune recovery and associated antiviral and antitumor response.…”
Section: Hsc and Pdc Mobilization And Engraftmentmentioning
confidence: 99%